Physics of Gravity: Comments and Criticism of the Theory of Relativity (Global Journal of Science Frontier Research, 2024)
The proposed article is an analytical review of previously published articles in the series Physics of Gravity and The picture of the world according to the second law of thermodynamics The main topic is the physics of gravity This article presents the proposed hypothesis on the physics of gravity in a brief form A critique of existing views on the topic of gravity is also presented Currently the generally accepted and dominant theory in the field of gravity is the General Theory of Relativity The proposed hypothesis is based on the concepts and laws of classical Newton physics At the same time a critique of the existing theory of gravity based on postulates conventions and assumptions is presented
Keywords: physics of gravity; gyroscopic forces of rotation of electrons; temperature dependence